KUALITAS SUNGAI SELAGAN BENGKULU BERDASARKAN FISIKA-KIMIA PERAIRAN DAN KERAGAMAN MAKROINVERTEBRATA - Abdul Rahman Singkam; Zakaria Husni; K Kasrina (Jurnal Biosilampari : Jurnal Biologi, 2022)
This research aims to determine the quality of Selagan River, Bengkulu based on its water physico-chemical parameters and macroinvertebrate diversity. Data were collected at three stations, Lubuk Bangko (upstream), Lubuk Sahung (middle) and Tanah Rekah (downstream) in April 2019 represents the peak of rainy season, and September 2019 represents the peak of dry season. Macroinvertebrate sampling was carried out on three minutes sampling method, and the obtained samples were identified at least to the family level. The result indicated the physico-chemical of Selagan River are generally in a normal range, except for a bit higher temperature at Lubuk Sahung and Tanah Rekah during April sampling (31 and 32oC respectively). This research also found 508 of individual macroinvertebrates that were divided into 19 species (19 families; 4 class and 4 phyla). The Shannon wienner diversity index (H’) of macroinvertebrates from the upstream to downstream are 1.54; 2.20 and 0.84, while the Berger-Parker’s dominance index (BP) are ranging from 0.30 into 0.92. The number of EPT individual in each station from up- to downstream is 129; 40; and 0, with FBI index is 4.11; 5.23; and “infinity” consecutively. The combination of those several indices indicated that the upstream of Selagan river is still in a very good condition, the middle area is starting to degraded, while the downstream had been degraded and polluted by organic substances.